1997
DOI: 10.1038/sj.onc.1200813
|View full text |Cite
|
Sign up to set email alerts
|

Identification of p53 genetic suppressor elements which confer resistance to cisplatin

Abstract: Loss of p53 function is associated with the acquisition of cisplatin resistance in the human ovarian adenocarcinoma A2780 cell line. Selection for cisplatin resistance of A2780 cells was used to isolate genetic suppressor elements (GSEs) from a retroviral library expressing random fragments of human or murine TP53 cDNA. Six GSEs were identified, encoding either dominant negative mutant peptides or antisense RNA molecules which corresponded to various regions within the TP53 gene. Both types of GSE induced cisp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
44
0

Year Published

2000
2000
2007
2007

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 80 publications
(49 citation statements)
references
References 19 publications
(33 reference statements)
5
44
0
Order By: Relevance
“…It should be noted that many of the studies to define the impediment caused by mutant p53 have been conducted in tumor model systems. There is little doubt from several such studies that downregulation of the apoptotic process in tumor cells expressing mutant p53 is a major mechanism contributing to cisplatin resistance (Fan et al, 1994;Eliopoulos et al, 1995;Perego et al, 1996;Gallagher et al, 1997;Righetti et al, 1999). Since mutant p53 disrupts cell cycle arrest in G1, which is also the phase in which tumor cells are most sensitive to cisplatin, resistance due to loss in p53 function may be mediated in part by disruption in cell cycle checkpoints (Shah and Schwartz, 2001).…”
Section: Dysfunction Of Tumor-suppressor P53mentioning
confidence: 99%
“…It should be noted that many of the studies to define the impediment caused by mutant p53 have been conducted in tumor model systems. There is little doubt from several such studies that downregulation of the apoptotic process in tumor cells expressing mutant p53 is a major mechanism contributing to cisplatin resistance (Fan et al, 1994;Eliopoulos et al, 1995;Perego et al, 1996;Gallagher et al, 1997;Righetti et al, 1999). Since mutant p53 disrupts cell cycle arrest in G1, which is also the phase in which tumor cells are most sensitive to cisplatin, resistance due to loss in p53 function may be mediated in part by disruption in cell cycle checkpoints (Shah and Schwartz, 2001).…”
Section: Dysfunction Of Tumor-suppressor P53mentioning
confidence: 99%
“…Biologically active cDNA fragments are then isolated from cells expressing the library by a positive functional selection for a specific phenotype. This concept has been used previously to identify functional regions in several genes including topoisomerase II (9), kinesin heavy chain (10,11), and p53 (12,13). Here we adjusted the screen to the conditions and principles of the TKO selection procedure (1).…”
mentioning
confidence: 99%
“…7 Because apoptosis is a genetically programmed cellular response to environmental stresses or stimuli, mutations in apoptotic pathways and the decreased susceptibility to apoptosis have been shown to be associated with cellular resistance to chemotherapeutic drugs and radiation treatment in various human cancers including lung cancer. [25][26][27][28][29][30][31] We previously showed that exogenous expression of FUS1 in FUS1-deficient NSCLC cells might effectively inhibit tumor cell growth and induce apoptosis in vitro and in vivo. 13,15 The overexpression of FUS1 in CDDP-treated NSCLC cells may overcome the cellular resistance and enhance the cellular response to the chemotherapy by facilitating the drug-induced apoptosis and other cell dead pathways.…”
Section: Discussionmentioning
confidence: 99%